Light harvesting complexes and chromatic adaptation of Eustigmatophyte alga Trachydiscus minutus - Pazderník, Marek (Jihočeská univerzita, 2015)
The chromatic adaptation of Trachydiscus minutus was investigated by separation of light harvesting complexes (antennae and photosystems) on a sucrose gradient using variety of detergents and their concentrations, further complex purification and characterization was done using biochemical separation and spectroscopic techniques.
Light harvesting complexes and chromatic adaptation of Eustigmatophyte alga Trachydiscus minutus